The other Black girl [large type] - Harris, Zakiya Dalila (Thorndike Press large print basic, 2021)
"Get Out meets The Devil Wears Prada in this electric debut about the tension that unfurls when two young Black women meet against the starkly white backdrop of New York City book publishing. Twenty-six-year-old editorial assistant Nella Rogers is tired of being the only Black employee at Wagner Books. Fed up with the isolation and microaggressions, she's thrilled when Harlem-born and bred Hazel starts working in the cubicle beside hers. They've only just started comparing natural hair care regimens, though, when a string of uncomfortable events elevates Hazel to Office Darling, and Nella is left in the dust. Then the notes begin to appear on Nella's desk: LEAVE WAGNER. NOW. It's hard to believe Hazel is behind these hostile messages. But as Nella starts to spiral and obsess over the sinister forces at play, she soon realizes that there's a lot more at stake than just her career. A whip-smart and dynamic thriller and sly social commentary that is perfect for anyone who has ever felt manipulated, threatened, or overlooked in the workplace, The Other Black Girl will keep you on the edge of your seat until the very last twist"--